IMPLEMENTASI MODEL PEMBELAJARAN SECARA LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR SISWA MI - Dwi, Musdalifa; Yahya, Muhammad (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2025)
This study aims to evaluate the implementation of the learning model directly in improving student learning outcomes at Madrasah Ibtidaiyah (MI). The research methods include theoretical analysis of direct learning models, evaluation of relevant previous research, and the preparation of conceptual frameworks that consider learning strategies, classroom management, and evaluation of learning outcomes. The results of the study show that the implementation of the direct learning model in Madrasah Ibtidaiyah (MI) proves significant potential to improve student learning outcomes. With a focus on direct interaction between teachers and students, clear explanations of material, and adaptation of learning to students' needs, this model enables improved understanding of concepts, application of religious values, and holistic learning outcomes. In the context of MI, where religious teachings and ethics play a central role, the direct learning model can make a positive contribution in accordance with educational objectives, bringing a positive impact on student learning outcomes.